COSMIC: High‐Resolution Cancer Genetics Using the Catalogue of Somatic Mutations in Cancer. (13th February 2018) - Forbes, S.A.; Beare, D.; Bindal, N.; Bamford, S.; Ward, S.; Cole, C.G.; Jia, M.; Kok, C.; Boutselakis, H.; De, T.; Sondka, Z.; Ponting, L.; et al.
Abstract: COSMIC (http://cancer.sanger.ac.uk ) is an expert‐curated database of somatic mutations in human cancer. Broad and comprehensive in scope, recent releases in 2016 describe over 4 million coding mutations across all human cancer disease types. Mutations are annotated across the entire genome, but expert curation is focused on over 400 key cancer genes. Now encompassing the majority of molecular mutation mechanisms in oncogenetics, COSMIC additionally describes 10 million non‐coding mutations, 1 million copy‐number aberrations, 9 million gene‐expression variants, and almost 8 million differentially methylated CpGs. This information combines a consistent interpretation of the data from the major cancer genome consortia and cancer genome literature with exhaustive hand curation of over 22, 000 gene‐specific literature publications. This unit describes the graphical Web site in detail; alternative protocols overview other ways the entire database can be accessed, analyzed, and downloaded. © 2016 by John Wiley & Sons, Inc.